Utility Tokens as a Commitment to Competition - GOLDSTEIN, ITAY; GUPTA, DEEKSHA; SVERCHKOV, RUSLAN (Journal of Finance, 2024)
ABSTRACT We show that utility tokens can limit the rent‐seeking activities of two‐sided platforms with market power while preserving efficiency gains due to network effects. We model platforms where buyers and sellers can meet to exchange services. Tokens serve as the sole medium of exchange on a platform and can be traded in a secondary market. Tokenizing a platform commits a firm to give up monopolistic rents associated with the control of the platform, leading to long‐run competitive prices. We show how the threat of entrants can incentivize developers to tokenize and discuss cases where regulation is needed to enforce tokenization.